Rising: A Feature Film - Devenport, Isaac (Auckland University of Technology, 2022)
This thesis consists of a full-length screenplay for a feature film. A summary of the screenplay is as follows: Rising is the story of Ezra (16), an average boy from a middle class family, sent away to St Augustine’s Catholic boarding school for boys, due to his mother’s (Jeanette) promotion. Ezra soon fits in with a group of boys, lead by alpha male Tony, and is even offered a university scholarship by the school dean, Father Mason. However, Ezra develops a relationship with another boy, Gary, and after several erotic and tender moments their friendship begins to blossom into romance, bringing Ezra’s safety and identity into question. As Ezra’s classmates misogynistic and homophobic behaviour gradually becomes more extreme, and his dissociation with the school’s masculine “bro” culture grows, Ezra seeks out the guidance of Peter, a queer, gender-bending musician. Ezra begins to experiment with his appearance through lipstick, pearl earrings and a golden jacket, and continues chasing a passionate and intimate romance with Gary, until Father Mason catches them and informs Jeanette. Jeanette makes its clear she doesn’t want a queer son and threatens Ezra with his father’s violence. Ezra becomes torn and beats up Peter, consequently forcing Peter to leave town, and leaving Ezra without a queer refuge. Despite this, Ezra and Gary are unable to fight their love and are soon caught by Tony, kissing in the forest. Tony lashes out at Ezra, and Gary is killed attempting to intervene. Devastated, Ezra is threatened by Tony and Father Mason to keep his mouth shut. However, Ezra blurts out everything to the police, but is ignored when the other boys deny his claims. Trapped and isolated, Ezra breaks free by putting on his queer regalia and confronting Tony with a rifle before the entire school. Tony wets himself in fear, disempowering him, and Ezra is witnessed as unapologetically queer. Ezra leaves school and his family behind to begin a new journey. Rising deals with masculinity and heteronormativity, and the expectations and consequences that they bring - the struggle of an emerging queer identity, and the cost one must pay in order to live as their true self. The Thesis is framed by an Exegesis which is a 6000 word essay on the subject of: (a) the genre of the Thesis (b) the development process from synopsis to second draft.
Keywords: Script; Thesis; Feature film; Queer; Creative writing; Coming of age